236 Systemic mitochondrial dysfunction in monogenic Parkinson's disease as a potential biomarker for stratification. Issue 6 (27th May 2022) - Campbell, Philip; Harvey, John; Morris, Huw; Schapira, Anthony
Abstract : To investigate the use of PBMCs as a biomarker of mitochondrial dysfunction in Parkinson disease (PD) fresh peripheral blood mononuclear cells (PBMCs) were isolated using Ficoll gradient separation from PD patients with pathogenic biallelic parkin mutations as well as healthy controls (HC). PBMC mitochondrial function was analysed using Seahorse XF respirometry and flow cytometric assessment of mitochondrial membrane potential (Δψm) using TMRE staining. Nine parkin PD patients (average age 45.2yrs, 66% male) and 41 healthy controls (average age 57.8yrs, 58% female) were sampled for the study. Parkin patients had increased oxygen consumption related to proton leak, reduced maximal respiration and reduced spare respiratory after correction for age (p<0.01). Additionally Parkin patients were found to have reduced resting Δψm and reduced oxygen consumption related to ATP production (p<0.01). Basal oxygen consumption was similar between Parkin patients and healthy controls. These findings are in keeping with parkin's role in removing dysfunctional mitochondria through mitophagy. The finding of normal basal oxygen consumption suggests that dysfunction is most pronounced when cells are under stress, during high ATP demand. This 'signature' of mitochondrial dysfunction could be applied to idiopathic PD patients to define a mitochondrial subgroup, in which personalised, stratified therapeutics could be targeted. p.campbell@ucl.ac.uk